2017
DOI: 10.1371/journal.pone.0174173
|View full text |Cite
|
Sign up to set email alerts
|

High MELD score and extended operating time predict prolonged initial ICU stay after liver transplantation and influence the outcome

Abstract: BackgroundThe aim of the present study is to determine the incidence of a prolonged (>3 days) initial ICU-stay after liver transplantation (LT) and to identify risk factors for it.Patients and methodsWe retrospectively analyzed data of adult recipients who underwent deceased donor first-LT at the University Hospital Essen between 11/2003 and 07/2012 and showed a primary graft function.ResultsOf the 374 recipients, 225 (60.16%) had prolonged ICU-stay. On univariate analysis, donor INR, high doses of vasopressor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 29 publications
2
12
0
Order By: Relevance
“…Several studies used either single‐center analysis or registry data to focus on the C1 risk model for mortality after LT. Importantly, although previous risk factor analyses included the MELD score as a preoperative predictor using C1 variables, in the present study, similar to a previous meta‐analysis, it was not an independent risk factor. Observation of a significantly improved AUC of the C1 risk calculator model for mortality versus the previously reported equations from single‐center analyses indicates an effectiveness of these novel risk calculator models.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…Several studies used either single‐center analysis or registry data to focus on the C1 risk model for mortality after LT. Importantly, although previous risk factor analyses included the MELD score as a preoperative predictor using C1 variables, in the present study, similar to a previous meta‐analysis, it was not an independent risk factor. Observation of a significantly improved AUC of the C1 risk calculator model for mortality versus the previously reported equations from single‐center analyses indicates an effectiveness of these novel risk calculator models.…”
Section: Discussionsupporting
confidence: 55%
“…The postoperative clinical course after LT should be determined by preoperative/postoperative recipient conditions and donor allograft conditions. Many studies have investigated the preoperative and intraoperative risk factors of recipient‐related or allograft‐related DDLT and LDLT recipients . However, to our knowledge, a large population study investigating both recipient and donor allograft conditions based on registry data has not been carried out to date.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, we analyzed a potential allocation bias by comparing match frequencies of marginal livers and marginal recipients. Marginal livers were defined as donor age > 60 years [ 17 ], BMI > 25 kg/m 2 [ 18 ] and cold ischemia time > 12 hours [ 19 ], while marginal recipients were defined as those with a MELD > 35 or HU-status [ 20 ]. In addition, we calculated the donor risk index (DRI, [ 17 ]) for every patient.…”
Section: Resultsmentioning
confidence: 99%
“…Regarding length of stay in the ICU, Pedersen and associates, 17 in a study of factors associated with a longer stay in the ICU, found that pretransplant MELD was the most potent predictor of prolonged ICU stay. Stratigopoulou and colleagues 18 confirmed that MELD and transplant duration are independent predictors of prolonged ICU stay. However, Rana and associates 19 hospital stay, the 2 most significant were shown to be previous admission of the recipient to the ICU (odds ratio of 1.75; 95% CI, 1.58-1.95) and previous transplant (odds ratio of 1.60; 95% CI, 1.47-1.75).…”
Section: Discussionmentioning
confidence: 91%